MOTIVASI DAN KETERAMPILAN PEMAHAMAN TEHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DENGAN STRATEGI THINK TALK WRITE - Rizqiyani, Putri Okti; Utami, Wikan Budi; Isnani, Isnani (Universitas Muhammadiyah Purworejo, 2019)
This study aims to analyze how the influence of 1) motivation on mathematical problem solving skills with TTW strategy, 2) skills of understanding of mathematical problem solving skills with TTW strategies, 3) motivation and skills understanding of mathematical problem solving skills with TTW strategies. Data collection techniques using tests, questionnaires, and observations. The test instrument for problem solving ability amounted to 10 items, the questionnaire amounted to 30 items, while the observation instrument amounted to 15 items. Test instruments and questionnaires were first tested in the trial class to determine validity and reliability. Data analysis using a simple linear regression test and multiple regression, with a significance level of 5%. The results were obtained 1) motivation influences the ability of mathematical problem solving with TTW strategy with a degree of influence 60.59%, 2) comprehension skills affect the ability to solve mathematical problems with TTW strategies with an effect of 59.3%, 3) motivation and comprehension skills affect the ability to solve mathematical problems with the TTW strategy with a 65.99% effect.Keywords: Motivation, Understanding Skills, Mathematical Problem Solving Ability, Think Talk Write Strategy